Etiology of atrial fibrillation in patients with complex congenital heart disease — for a better treatment strategy. Issue 5 (November 2020) - Miyazaki, Aya; Negishi, Jun; Hayama, Yohsuke; Tsuda, Etsuko; Yamada, Osamu; Ichikawa, Hajime; Uemura, Hideki; Ohuchi, Hideo
Highlights: Atrial fibrillation (AF) in complex congenital heart disease (CHD) correlates with a higher right atrial (RA)-sided overload. AF in complex CHD had a high incidence of a persistent left superior vena cava and high mortality rate. In a substantial number, RA-sided interventions were effective to control AF. Abstract: Background: The demographics of patients with congenital heart disease (CHD) and atrial fibrillation (AF) differ significantly from the general population. The etiology and treatment strategy for AF in CHD patients have been investigated but are to date inconclusive. Methods: To determine the etiology of AF in CHD and to seek a better treatment strategy, we retrospectively evaluated the atrial overload in 42 complex CHD cases with normal atrial arrangements and AF (age 25; range, 9–66 years) and the impact of a reduction in the atrial overload on the atrial rhythm. Results: Cardiac defect diagnoses varied, with 17% of the patients having a persistent left superior vena cava (PLSVC). In regard to the volume overload, the frequencies of an overload in the right atrium (RA), left atrium (LA), or both, were 50 %, 23%, and 10%, respectively ( p  = 0.015). Other sustained supraventricular tachycardias were observed in 29 patients (69%) before and after the onset of AF. Among these 29 patients, 26 had intra-atrial reentrant tachycardia. Fifteen patients (36%), 10 of whom had chronic AF, died during the follow-up including 3 with arrhythmias and 10 because of heart failure. Fourteen (33%) patients had no AF at the last follow-up due to medical interventions, 8 of which underwent solely an RA-sided catheter ablation and/or surgical RA overload reduction. Conclusions: AF in complex CHD with a normal atrial arrangement correlates with a higher RA-sided overload than an LA-sided and exhibits a high incidence of PLSVCs, high comorbidity of intra-atrial reentrant tachycardias, and high mortality rate. In a substantial number of patients, RA-sided interventions were effective in controlling AF. To effectively manage AF in complex CHD it is essential to understand each individual's hemodynamics and consider hemodynamic interventions.